Relaxivity properties of superparamagnetic iron oxide nanoparticles incorporated into silica nanoparticles via ultrasonic irradiation / Bashiru Kayode Sodipo …[et al.] - Sodipo, Bashiru Kayode; Carreras Diaz, Willy; Azlan, Abdul Aziz; Gonzalez Dalmau, Evelio Rafael (Faculty of Applied Sciences, 2023)
Herein, we report the relaxivity property of Superparamagnetic Iron oxide Nanoparticles (SPION) incorporated into a silica nanoparticle framework. The SPION/Silica is synthesized via a non-seeded process of colliding as-synthesized SPION into a silica nanoparticle framework via ultrasonic irradiation. Both SPION and silica nanoparticles were synthesized independently. Then, the tremendous energy plus other unique conditions generated from ultrasonic irradiation were employed to accelerate, collide and incorporate SPION into silica nanoparticles. T2 and T1 relaxivity properties of the SPION/silica were measured in the Agarose gel phantom using a 1.5 T MRI scanner. Results revealed that the SPION/silica influence T2 contrast in a concentration-dependent manner.